Quadrature rules from a R I I type recurrence relation and associated quadrature rules on the unit circle - Bracciali, Cleonice F. [UNESP]; Pereira, Junior A. [UNESP]; Ranga, A. Sri [UNESP] (Springer Nature, 2019)
We consider the theoretical and numerical aspects of the quadrature rules associated with a sequence of polynomials generated by a special R II recurrence relation. We also look into some methods for generating the nodes (which lie on the real line) and the positive weights of these quadrature rules. With a simple transformation, these quadrature rules on the real line also lead to certain positive quadrature rules of highest algebraic degree of precision on the unit circle. This way, we also introduce new approaches to evaluate the nodes and weights of these specific quadrature rules on the unit circle.
Keywords: Orthogonal polynomials on the unit circle; Quadrature rules; R II type recurrence relation